Transitioning to emergency online teaching: The experience of Spanish language learners in a US university. (February 2022) - Ruiz-Alonso-Bartol, Ana; Querrien, Diane; Dykstra, Shelley; Fernández-Mira, Paloma; Sánchez-Gutiérrez, Claudia
Abstract: This study documents students' experiences during the Emergency Online Transition of Spring 2020 in a Spanish language program at a large public university in the United States. Data from students' mid-term and end-of-term questionnaires, as well as teachers' journals, were collected in the Spring, and follow-up teacher interviews were carried out in Fall 2020. Results indicate that students' overall stress levels diminished from beginning to end of the academic term but that individual experiences were extremely varied. While some students enjoyed the increased autonomy and self-paced learning opportunities of the online format, others felt distressed in this less directed modality and emphasized the negative effect of reduced social interactions on their levels of engagement. Only few students mentioned technological difficulties as a central challenge in their learning process, but many believed that they had learned less than in traditional face-to-face courses. Instructors' views differed in this respect, as they considered that the reduced group-size of synchronous Zoom sessions allowed them to hear more of each student, which they saw as evidence of increased student talk as compared to the usual whole-class face-to-face sessions. This more intimate virtual set-up also increased a sense of proximity between teachers and students. Highlights: "Sense of community" impacts above all the perception of emergency online education. Teachers' culture of adaptation is critical to face crisis-prompted change. Students' development of autonomy in online education requires explicit support. Future research should explore avenues for community building in online education.